Ecotourism Management Training with Creative Economy Development for Communities in Ecotourism Areas - Subhan, Subhan; Taupan, Taupan; Bakri, Asriady; Arsyad, Muhammad; Karmin, Rhomariotha Chabeyrumania Bin; Prasetyo, Dito (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This research aims to increase the capacity of the Kapita Village community, Bangkala District, Jeneponto Regency, to manage ecotourism based on the creative economy. Through the Community Service (PkM) program, training was conducted on ecotourism and creative economic development, with active participation from the community and local village officials. Research Design and Methodology: The methodology includes direct education through material presentations, discussions, and question-and-answer sessions. This activity was carried out on November 9, 2024, at the Kapita Village Office, with participants consisting of the community and village officials. Data was collected through participatory observation and in-depth interviews, then analyzed descriptively qualitatively to identify changes in participants' understanding and attitudes towards ecotourism management and creative economy. Findings and Discussion: The results showed a significant increase in the community's understanding of ecotourism and creative economic concepts. There was an increased interest in starting small businesses supporting ecotourism, such as souvenir-making and tour guide services. However, inadequate infrastructure and environmental awareness still hinder effective ecotourism development. Implications: The implications of these findings suggest the need for collaboration between government, communities, and other stakeholders to provide sustainable training programs and infrastructure investments. This is important to improve the accessibility and quality of ecotourism destinations and encourage active community participation in creative economic development. Future research is recommended to conduct long-term evaluations of the impact of training programs and explore strategies to diversify tourist attractions to increase resilience to climate change and tourism market dynamics.